Timing and Location of Spawning Based on Larval Capture and Ultrasonic Telemetry of Atlantic Sturgeon in the Saint John River, New Brunswick. Issue 2 (1st February 2017) - Taylor, Andrew D.; Litvak, Matthew K.
Abstract: The timing and location of spawning of Atlantic Sturgeon Acipenser oxyrinchus oxyrinchus were investigated using larval sampling and ultrasonic telemetry in 2010–2014 in the lower Saint John River, New Brunswick, Canada. Larval sampling was conducted to identify potential spawning areas using anchored D‐frame drift nets and towed bongo nets. Forty‐four adult Atlantic Sturgeon (138–213 cm) were ultrasonically tagged and passively tracked using hydrophone receivers located throughout the river. Spawning was confirmed with the first capture of Atlantic Sturgeon larvae in the river. Four Atlantic Sturgeon yolk sac larvae (13.44–14.43 mm) were captured on July 23, 2011, and one exogenous feeding larva (22.6 mm) on July 25, 2011, at river kilometer (rkm) 106 near Burton, New Brunswick. Spawning time was estimated using larval growth models and is likely to have occurred July 6–13, 2011, above rkm 106. Eleven tagged fish returned to the river in May and June after a minimum of 2 years at large: nine males, one female, and one unknown sex. Seven of the 11 returning fish migrated to potential spawning areas above rkm 100. Based on the upstream occupancy observed, annual variability in spawning time is likely. The other four fish that returned remained below the salt–fresh interface with brief upstream migrations below rkm 100, suggesting that some fish are not spawning during summer migration. The majority of fish migrated from the river in August and September. This study provides the first description of the location and timing of Atlantic Sturgeon spawning and migratory patterns in the Saint John River. Received April 3, 2016; accepted November 17, 2016 Published online February 1, 2017